Aesthetics, politics, and sociolinguistic analysis. (January 2018) - Pratt, Mary Louise
Abstract: This paper argues that aesthetic analysis is a necessary tool for sociolinguistic explication, especially of translingual and intercultural verbal activity, and especially for understanding its political dimensions. The suggestion is that to grasp what Doris Sommer has called the 'real world of living language' (2004: 34), sociolinguistics needs analytical tools to make explicit the aesthetic dimensions of the materials it studies. I explore this question using theories of democracy and examples from the contemporary language-scape in the United States.